Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4314/ajbr.v4i3.53888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continous light and darkness exposures on the petuitary-gonadal axis and thyroid activity in male rats

Abstract: The effects of constant light and dark exposure of pubertal male rats on the pituitary-gonadal axis and thyroid activity were studied. The indices of thyroid activity were weight of the thyroid gland, estimation of serum levels of thyroxine (T 4) by radioimmunoassay (RIA) technique and histological studies of the thyroid gland. The indices of gonadal activity chosen were weight and histological study of the testes and determination of serum levels of Luteinizing hormone (LH) and Follicle Stimulating Hormon (FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In the present work, light microscopic findings in rats exposed to constant light for short period (1 month) revealed that the thyroid gland was stimulated, as evidenced by microfollicular thyroid structure and little or no colloid in the thyroid follicles. Similar results were detected by Olatunji and Sofola [30]. Belviranli and Baltaci [3] reported that the activity of the pineal gland increased and thyroid growth was inhibited in male rats under light restriction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present work, light microscopic findings in rats exposed to constant light for short period (1 month) revealed that the thyroid gland was stimulated, as evidenced by microfollicular thyroid structure and little or no colloid in the thyroid follicles. Similar results were detected by Olatunji and Sofola [30]. Belviranli and Baltaci [3] reported that the activity of the pineal gland increased and thyroid growth was inhibited in male rats under light restriction.…”
Section: Discussionsupporting
confidence: 85%
“…It has given rise to the concept that melatonin is the chemical expression of darkness. Continuous exposure to light leads to a complete suppression of melatonin release [9,30].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that any study involving hypothalamic TRH determination should be consider the diurnal variation and the effect of environmental light exposure [7] . When compared with the rats exposed to normal lighting rhythm, continuous darkness exposure resulted in a decrease in the thyroid activity as well as a remarkable decrease in gonadal activity in male rats [8] .However, what is the influence of continuous light, darkness and exogenous melatonin on serum levels of melatonin? Is it similar to circadian rhythm or not?…”
mentioning
confidence: 94%
“…Previous studies also show that prolonged darkness phase can change the serum level of some hormones in body [15]. For example several studies show that prolonged darkness phase in photoperiodic cycle causes decreased serum level of T3 [16], [17], whereas there is a study indicating that prolonged darkness phase has no effect on secretion of T3 hormone [18]. The probable mechanism of action could be referred to the effect of prolonged darkness phase on systems such as immunity and gonadal system [19]- [21], which in turn, may result in increased serum level of creatine kinase and alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%